Studi Eksperimental Rancang Bangun Alat Pencetak Briket Berbasis Dinamo Servo Kapasitas 6 Kg - Lekatompessy, Frendris Allesandro; Kusumawardana, Ahmad Rizal Nurul; Dayera, Disabella (Rekayasa Material, Manufaktur dan Energi, 2025)
Research on the design of a servo dynamo-based briquette printer is a relevant research topic in the development of briquette production technology to support the utilization of biomass as a sustainable alternative energy source. The purpose of this research is to design a servo dynamo-based briquette printer with a capacity of 6 kg using the experimental method, where the test parameters are machine performance, printing operational parameters and briquette quality. The research results obtained are a briquette printing machine made with overall system dimensions of 23 cm high, 50 cm long and 25 cm wide, using a servo dynamo with a power capacity of 550 watts and a gearbox (ratio 1: 60). The results obtained are that the engine torque value obtained is 60 N.m and the maximum speed of 60 RPM has a machine efficiency value of 75.4%, where the high efficiency value contributes to more efficient energy consumption and has stable productivity, which is for a capacity of 6 kg capable of producing 180 briquettes for 12.32 minutes with an average production time per briquette of 4.2 seconds. The quality of the briquette test results from the machine made has a moisture content of 6.25% and a briquette density of 533.33 Kg⁄m3. Overall, the use of servo dynamo in the briquette molding machine is able to improve production efficiency and has fulfilled SNI 01-6235-2000.